Parenting Styles and Short- and Long-term Socialization Outcomes: A Study among Spanish Adolescents and Older Adults - Oscar F. García (Psychosocial Intervention, 2018)
In this study, the association between parenting styles and short- and long-term socialization outcomes was analyzed using a two-dimensional model of four types of parenting styles. The socialization outcomes analyzed were self-esteem and internalization of social values. Participants were a sample of Spanish adolescents (n = 571) and older adults (n = 527). Results showed that both adolescents and older adults from indulgent families reported equal or even higher self-esteem than those from authoritative households, whereas those from neglectful and authoritarian homes were consistently associated with the lowest levels of self-esteem. Regarding internalization of social values, adolescents and older adults raised in indulgent and authoritative families prioritized self-transcendence values (universalism and benevolence) and conservation values (security, conformity, and tradition) as compared to those from authoritarian and neglectful homes, whereas those from neglectful and authoritarian families showed lower scores in all internalization of social values measures. These results suggest that the combination of high levels of parental warmth and involvement and low levels of strictness and imposition (i.e., indulgent parenting style) is an optimum parenting strategy in the cultural context where the study was conducted, and that the link between parenting styles and socialization outcomes share a common short- and long- term pattern.